Education and Training Needs in the Field of Agriculture and Rural Development in the Lower Danube Region - Nicolae Istudor; Margarita Bogdanova; Victor Manole; Raluca Ignat; Irina Elena Petrescu (Amfiteatru Economic)
Given the conditions of European Strategy for Labour which was ratified also by Romania, that states an intensifying implementation at national level of labour policies and especially those regarding young person labour market integration, and taking into consideration the great human and agricultural potential of Lower Danube Region, we consider the implementation of national and regional programmes in order to train agriculture and rural development specialists to be very necessary. This article inquires the necessity of training agriculture and rural development specialists within Lower Danube Region in the context of cross-border cooperation between Romania and Bulgaria. This research starts by analysing the European and national legal framework of adult training in those two fields. Subsequently, the main premises and advantages of those activities were emphasized. It is good to mention that the Academy of Economic Studies in Bucharest, Romania, and the D. Tsenov Academy of Economics in Svishtov, Bulgaria, proposed themselves to cooperate in the field of “human resources development – common development of skills and knowledge”. The legal base exists as the Romania-Bulgaria Cross-border Cooperation Programme 2007-2013 is enforced. Furthermore, a four years comparative study of the number of persons trained for the main jobs in rural area, including farmer, in Lower Danube Region was conducted. All these led to the idea that it is necessary to continue and to stress adult training of farmers and rural specialists as a solution for rural economy development and social welfare. Also, comparative analysis of supply and demand of professionals in the field of agriculture was elaborated. The main educational programs in training agriculture and rural development specialists were identified and some problems and perspectives were worked out. This research can be considered as a first step of future deeper and profound collaboration of Tsenov Academy of Economics, Svishtov and the Academy of Economic Studies, Bucharest in terms of creation of common Romanian-Bulgarian Research Area, as a part of European Research Area (ERA). It includes joint knowledge and skills development through cross-border linkages and exchanges between the universities, in accordance with Romania – Bulgaria Cross-Border Cooperation Programme 2007-2013